Acceptance of private doctors towards privatization of monitoring foreign workers medical examination in Gombak and Petaling district, 1998 - Mahani Ahmad Hamidy,; Syed Mohamed Aljunid, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A research which combines qualitative and quantitative technique was conducted to study the acceptance of private